France in the South Pacific Power and Politics - Fisher, Denise (ANU Press, 2013)
France is a Pacific power, with three territories, a military presence, and extensive investments. Once seen by many as a colonial interloper in the South Pacific, by the early 2000s, after it ended nuclear testing in French Polynesia and negotiated transitional Accords responding to independence demands in New Caledonia, France seems to have become generally accepted as a regional partner, even if its efforts concentrate on its own territories rather than the independent island states. But France's future in the region has yet to be secured. By 2014 it is to have handed over a set of agreed autonomies to the New Caledonian government, before an independence referendum process begins. Past experience suggests that a final resolution of the status of New Caledonia will be divisive and could lead once again to violent confrontations. In French Polynesia, calls continue for independence and for treatment under UN decolonisation procedures, which France opposes. Other island leaders are watching, so far putting faith in the Noumea Accord, but wary of the final stages. The issues and possible solutions are more complex than the French Pacific island population of 515,000 would suggest. Combining historical background with political and economic analysis, this comprehensive study offers vital insight into the intricate history - and problematic future - of several of Australia's key neighbours in the Pacific and to the priorities and options of the European country that still rules them. It is aimed at policy-makers, scholars, journalists, businesspeople, and others who want to familiarise themselves with the issues as France's role in the region is redefined in the years to come.